Escolhas Sistêmicas de Transitividade e de Léxico na Representação de Escândalos Políticos: A Construção de Realidades de Crise e de Corrupção - Guilherme Rocha Brent (2011)
The present study investigates how the magazine VEJA builds, at systemic choices of transitivity and lexicon, systems of knowledge and meaning for three political scandals, namely: mensalão, dossiê and cartões corportativos political scandals, represented by reportages. Its main focus is to examine, at these systemic choices, how journalists build realities of crisis and corruption for the scandals. Thus, we use the System of Transitivity (HALLIDAY and MATTHIESSEN, 2004) and naming choices made by journalists, to interpret the realities of the scandals from the relationship between processes, their participants and circumstances. This research proposal is justified, within Linguistics, as a possibility to examine political scandals as discourses, namely, as particular ways of representing, through language, aspects of the world. Due to the crucial role of media in representation of these phenomena, we are assuming that political scandals are not constituted only by acts of transgression, but also by discourses. The disclosure, evaluation and sentencing of scandals in media not only describe a state of affairs. Rather, they are actions which partially constitute this state of affairs, integrating journalistic narratives to the existence of scandals. Thus, this research addresses representation in three aspects: first, every clause serves to express our experience of the world that is around us and inside us (HALLIDAY and MATTHIESSEN, 2004); second, every choice of representation is as much a matter of vocabulary as a matter of grammar (FAIRCLOUGH, 1995a); and third, every representation is a political activity which reflects the predilections of the one who builds it (RAJAGOPALAN, 2003). The theoretical and methodological base is the Critical Discourse Analysis, as understood by Norman Fairclough, and the Systemic Functional Linguistics, addressed in the studies of Halliday (1978) and Halliday e Matthiessen (2004). It also draws on the sociologist John Thompson studies about the notion of political scandal, in order to observe the characteristics of this kind of phenomenon, and some general principles of media action in contemporary life. The corpus consists of six reportages from the magazine VEJA. It was selected the first two articles published about each scandal, since at these first two editions journalistic texts already fulfilled the elements of a political scandal (THOMPSON, 2002). The results point out an excessive visibility of the transgressions, as well as their authors. When journalists introduce actions, define and classify, report utterances, express inner experiences, represent the existence of something and express psychological and physiological behaviors about the scandals, they build specific realities of the world to each event, potentiating their irregularities. In this discursive process, we can realize how each systemic choice is motivated by the improbity contexts of scandals. At the same time, we note that the discursive space given to the representation of the scandals is populated by a speech far more concerned to criticize and condemn the accused than rise the readers. awareness about the values of politics in a democratic society. We also realize that the magazine VEJA prints their points of view on the facts by choices of naming, trying to influence public opinion against the illegal activities committed in such scandals.